PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGANTISIPASI KECANDUAN SOSIAL MEDIA DAN MENJAGA KESEHATAN MENTAL SISWA DI MTS NEGERI 15 JOMBANG - Muhammad Ariful Amin; Sholihul Anshori (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Social Media is a technology used to communicate as well as to access available content. Social media if used excessively will result in addiction, for this reason anticipation or prevention is needed. On the other hand, students’ mental health also needs to be maintained, because with a healthy mentality students will more easily understand the learning taught by the teacher in class and will be more active in participating in activities. The research used a qualitative approach and the type was a case study. Data collection techniques using observation, interviews and documentation. Analyzing data through data reduction, presenting data and concluding data. The role of Islamic Religious Education in anticipating social media addiction and maintaining students’ mental health at MTs Negeri 15 Jombang is realized through learning social media adab to wisely use social media, as well as by participating in religious-based activities carried out regularly by students, aiming to anticipate social media addiction and maintain students’ mental health.